Identification of GGC repeat expansion in the NOTCH2NLC gene in amyotrophic lateral sclerosis. (15th December 2020) - Yuan, Yanchun; Liu, Zhen; Hou, Xuan; Li, Wanzhen; Ni, Jie; Huang, Ling; Hu, Yiting; Liu, Pan; Hou, Xiaorong; Xue, Jin; Sun, Qiying; Tian, Yun; et al.
Abstract : Objective: To determine whether the GGC repeats in the NOTCH2NLC gene contribute to amyotrophic lateral sclerosis (ALS). Methods: In this study, 545 patients with ALS and 1, 305 healthy controls from mainland China were recruited. Several pathogenic mutations in known ALS-causative genes (including C9ORF72 and ATXN2 ) and polynucleotide repeat expansions in NOP56 and AR genes were excluded. Repeat-primed PCR and GC-rich PCR were performed to determine the GGC repeat size in NOTCH2NLC . Systematic and targeted clinical evaluations and investigations, including skin biopsy and dynamic electrophysiologic studies, were conducted in the genetically affected patients. Results: GGC repeat expansion was observed in 4 patients (numbers of repeats 44, 54, 96, and 143), accounting for ≈0.73% (4 of 545) of all patients with ALS. A comparison with 1, 305 healthy controls revealed that GGC repeat expansion in NOTCH2NLC was associated with ALS (Fisher exact test, 4 of 545 vs 0 of 1, 305, p = 0.007). Compared to patients with the neuronal intranuclear inclusion disease (NIID) muscle weakness–dominant subtype, patients with ALS phenotype carrying the abnormal repeat expansion tended to have a severe phenotype and rapid deterioration. Conclusion: Our results suggest that ALS is a specific phenotype of NIID or that GGC expansion in NOTCH2NLC is a factor that modifies ALS. These findings may help clarify the pathogenic mechanism of ALS and may expand the known clinical spectrum of NIID.